Crick's sequence hypothesis - a review. Issue 1 (1st January 2019) - Baverstock, Keith
ABSTRACT: Health care based on gene sequencing and genomics is increasingly becoming a reality: it is timely to review Crick's sequence hypothesis for its fitness for this purpose. The sequence hypothesis is central to the prediction and correction of disease traits from gene sequence information. Considerable success in this respect has been achieved for rare diseases, but for the dominant part of the human disease burden, common diseases, little progress has been made since the completion of the sequencing of the human genome. It is argued here that the sequence hypothesis, namely the assumption that peptides will fold spontaneously to the native state protein, thus retaining the information coded in the originating genes, is not supported by a realistic physics-based assessment of the peptide to protein folding process.